KONSEP PERTAHANAN SEBAGAI PUBLIC GOOD ATAU MONOPOLI ALAMIAH MENURUT SISTEM EKONOMI KERAKYATAN - Endro Tri Susdarwono (JURNAL CAFETARIA, 2021)
The purpose of this study is to provide an overview of the debate about the economic concept which states that defense is a public good and which states that defense is not a public good but a natural monopoly based on understanding according to the market economy system and the populist economic system. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. The approach in this study uses a descriptive approach. Is national defense public goods purely (public good)? We can divide this question into three parts. (1) Is the national defense of goods? (2) Does national defense have the characteristics of jointness? (3) And whether national defense has characteristics without exception (non-exclusion). Association in the sense of controlling the lives of many people is all branches of production of goods and services whose results are used by everyone, or almost everyone. So defense as a product can be interpreted as a branch of production that controls the lives of many people because it can be said that defense is the same concept as the concept of "basic needs". All people in the country of Indonesia need defense and this is also reinforced with the aim of having a state in paragraph IV of the Preamble of the 1945 Constitution "Then to form an Indonesian government that protects all the people of Indonesia and all of Indonesia's blood." The results of this study state that the reason why the government supplies national defense is not because national defense is public goods. (1) that national defense is a natural monopoly and (2) citizens will fear that if a private company controls a monopoly, the owner of the company can use his power to overthrow the government.